A modeling approach to introduce haptic feedback in multimodal awareness for groupware systems - Rodríguez, Andrés (2023)
The key to effective collaboration is awareness; traditional groupware systems have relied on visual cues to achieve it. Audio has been used to complement and overcome the limitations of graphical displays to maintain awareness. However, the emergence of alternative user interface strategies, such as haptic feedback, presents new opportunities to promote awareness. Yet, designing effective haptic awareness mechanisms is challenging due to the lack of documented experience. Therefore, we suggest using flexible prototyping and evaluation tools to facilitate an exploratory design process. We also propose that the design of awareness features should consider modalities to be used and the relationships between them from the outset. To support this idea, we introduce a modeling language and supporting tools to express haptic awareness features. We show how the language can be used in the context of model-driven development of groupware.